Mismatch Repair Pathway, Genome Stability and Cancer - Pećina-Šlaus, Nives; Kafka, Anja; Salamon, Iva; Bukovac, Anja (Frontiers in Molecular Biosciences, 2020)
The acquisition of genomic instability is one of the key characteristics of the cancer cell, and microsatellite instability (MSI) is an important segment of this phenomenon. This review aims to describe the mismatch DNA repair (MMR) system whose deficiency is responsible for MSI and discuss the cellular roles of MMR genes. Malfunctioning of the MMR repair pathway increases the mutational burden of specific cancers and is often involved in its etiology, sometimes as an influential bystander and sometimes as the main driving force. Detecting the presence of MSI has for a long time been an important part of clinical diagnostics, but has still not achieved its full potential. The MSI blueprints of specific tumors are useful for precize grading, evaluation of cancer chance and prognosis and to help us understand how and why therapy-resistant cancers arise. Furthermore, evidence indicates that MSI is an important predictive biomarker for the application of immunotherapy.